Urgensi Pendidikan Karakter di Era Digital - Alvi Nur Azizah (putrapublisher.org, 2023)
This study aims to find out about the urgency of character education in the digital era. Education in the digital era is developing very rapidly, advances in technology are not only enjoyed by adults, elementary school-age children can also enjoy the results of current technological developments. In the world of education, technology can be used as a means and infrastructure in the learning process. Technological developments also have positive and negative impacts. Character education is the main foundation in the process of building character. Formation of character from an early age is very necessary. This research includes library research. The technique used is to analyze the soureces of literature in the form of literature, books, journals, records or the like. The results of this research are character education models including educational regulations, implementation of character education, exemplary, and discipline. Character education is needed to guide students in facing the digital era which is getting faster. The existence of character education can be a stronghold for students in the learning process to always prioritize the values ​​and norms that apply, but still keep abreast of existing developments.